The Effects of Firm Size, Leverage, and Accounts Receivable Turnover on Profitability: The Moderating Role of Institutional Ownership in Indonesian Consumer Non-Cyclical Companies - Monica Amelia Hidayat; Hendro Lukman (CV. Muris Global Education, 2026)
Profitability in the consumer non-cyclicals sector is an important indicator of firms’ operational sustainability and financial performance. This study examines the effects of firm size, leverage, and accounts receivable turnover on profitability, as well as the moderating role of institutional ownership. The study employed a quantitative explanatory design using 240 firm-year observations from consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2023–2025 period. The sample was selected through purposive sampling, and the data were analyzed using Moderated Regression Analysis (MRA). The findings show that firm size and institutional ownership have significant positive effects on Return on Assets (ROA). In contrast, leverage and accounts receivable turnover have significant negative effects on ROA. The interaction results indicate that institutional ownership significantly strengthens the positive effect of firm size on profitability and mitigates the negative effects of leverage and accounts receivable turnover on profitability. These findings suggest that institutional ownership plays an important monitoring role in improving financial decision-making and working capital efficiency. This study contributes to the corporate governance literature by providing empirical evidence on the role of institutional ownership in shaping the relationship between financial characteristics and profitability in Indonesian consumer non-cyclicals companies.